The Neoliberal University in Ireland: Institutional Bullying by Another Name? - Margaret Hodgins; Patricia Mannix-McNamara (Societies, 2021)
New managerialism and the pervasive neoliberalisation of universities is by now a well-established phenomenon. Commentaries explore the political and economic drivers and effects of neoliberal ideology, and critique the impact on higher education and academic work. The impact on the health and well-being of academic staff has had less attention, and it is to that we turn in this paper. Much academic interest in neoliberalism stems from the UK, Australia and the United States. We draw particularly on studies of public Irish universities, where neoliberalism, now well entrenched, but something of a late-comer to the new public management party, is making its presence felt. This conceptual paper explores the concept of neoliberalism in higher education, arguing that the policies and practices of new public management as exercised in universities are a form of bullying; what we term institutional bullying. The authors are researchers of workplace culture, workplace bullying and incivility. Irish universities are increasingly challenged in delivering the International Labour Organisation (ILO) principles of decent work, i.e., dignity, equity, fair income and safe working conditions. They have become exposed in terms of gender imbalance in senior positions, precariat workforce, excessive workload and diminishing levels of control. Irish universities are suffering in terms of both the health and well-being of staff and organisational vibrancy. The authors conclude by cautioning against potential neoliberal intensification as universities grapple with the economic fallout from the COVID-19 pandemic. This paper reviews neoliberalism in higher education and concludes with insight as to how the current pandemic could act as a necessary catalyst to stem the tide and ‘call out’ bullying at the institutional level.